Narative Review : Factors Related to the Occurrence of Diarrhea Among Under-Five Children - Resda Herliani; Riyan Ningsih; Akhmad Azmiardi (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Diarrhea in children under five years of age remains a significant global health crisis, particularly in developing countries, characterized by high morbidity and mortality rates. Although risk factors have been identified, geographic variations and the concentration of preventive interventions require a synthesis of updated evidence. Objective : This narrative review aims to provide a comprehensive update on the key determinants influencing diarrhea incidence in children aged 0-59 months. Research Methods/ Implementation Methods : The review was conducted on research articles published 2019-2024. The articles were retrieved from PubMed, Google Scholar, and ResearchGate databases, using keywords such as "toddlers," "diarrhea," and "determinants." The selection focused on studies reporting diarrhea prevalence, as well as risk or protective factors related to WASH (Water, Sanitation, and Hygiene), immunization, and sociodemographics. Inclusion criteria for articles were original research, written in Indonesian and English, and full papers. A total of 34 articles were analyzed narratively. Results : The prevalence of diarrhea in children under five in community-based studies varies (9.6% to 26.4%), with the highest incidence concentrated in the 6–23 month age group. Conclusion/Lesson Learned : The prevalence of diarrhea in children under five (9.6% to 26.4%). Children from families with low maternal education and limited socioeconomic resources are at greater risk. Strengthening access to safe water, sanitation, hygiene practices, and vaccination coverage is therefore essential for reducing diarrhea burden among under-five children.